INTEGRASI MODEL PEMBELAJARAN RESISTASI DAN FIELD TRIP TERHADAP HASIL BELAJAR DAN BERPIKIR KRITIS PADA KONSEP MATA KULIAH BIOSISTIMATIKA DAN EVOLUSI MAHASISWA SEMESTER VI PROGRAM STUDI PENDIDIKAN BIOLOGI - Tuaputty, Hasan; Wael, Syahran (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2022)
Background: Technological developments must be in line with lecture methods that make students havethe ability to study independently, learn to be more interesting, interactive, and easy to do, such as theintegration of the Resistasi lecture method and Field Trip learning methods which provide the widestopportunity for students to find and have the concept or material being studied. The purpose of this researchis to apply the recitation lecture method (assignment) and also the Field Trip method (tourist visits to certainplaces).Methods: This study uses a descriptive type by applying the Resistasi and Field Trip methods to theconcept or material of Biosystematics and Evaluation involving 31 students in the sixth semester of theBiology Education Study Program. Assessment is carried out on student learning outcomes and creativethinking is carried out by considering (1) the ability of students to carry out the integration of the Resistanceand Field Trip methods (2) The ability of students to answer critical thinking questions (3) The ability ofstudents to solve biosystematic and evolutionary knowledge questions (4 ) Assessment of skills andattitudes during the integration of the Resistance Method and Field Trip. To determine the effect of theintegration of the Resistasi and Field Trip methods, using the SPSS 20 program of Anova.Results: The Anova test on the integration of resistasi and field trip methods has an effect on mastery ofknowledge and critical thinking skills in biosystematics and evolution courses where the significant value is0.000, and the standard knowledge of coofecients beta is 0.802.Conclusion: the application of the integration course of the Resistasis and Field Trip methods onbiosystematics and evolutionary course materials for students of the biology education study programshowed a very good score.